2019
DOI: 10.3390/ijms20122933
|View full text |Cite
|
Sign up to set email alerts
|

Study on Structural Evolution, Thermochemistry and Electron Affinity of Neutral, Mono- and Di-Anionic Zirconium-Doped Silicon Clusters ZrSin0/-/2- (n = 6–16)

Abstract: We have carried out a global search of systematic isomers for the lowest energy of neutral and Zintl anionic Zr-doped Si clusters ZrSin0/-/2- (n = 6–16) by employing the ABCluster global search method combined with the mPW2PLYP double-hybrid density functional. In terms of the evaluated energies, adiabatic electron affinities, vertical detachment energies, and agreement between simulated and experimental photoelectron spectroscopy, the true global minimal structures are confirmed. The results reveal that struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…60,61 For the location of the cationic CrSi n + and neutral CrSi n isomers, initial guess structures are generated by considering stable geometries of cationic, anionic, neutral metal and non-metal doped Si clusters reported in the literature. 3,9,31,32,34,39,40,59,[62][63][64][65][66][67][68][69] Additionally, geometries of the pure Si clusters in different charge states taken from previous studies 31,34,37,42,44,[70][71][72][73] are used as starting structures on which the Cr atom is added at various positions or an atom of the Si frame is replaced by a Cr atom. These structures are subsequently optimized in different multiplicities, from the singlet to the septet state for systems with an even number of electrons, and from the doublet to the octet state for systems with an odd number of electrons.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…60,61 For the location of the cationic CrSi n + and neutral CrSi n isomers, initial guess structures are generated by considering stable geometries of cationic, anionic, neutral metal and non-metal doped Si clusters reported in the literature. 3,9,31,32,34,39,40,59,[62][63][64][65][66][67][68][69] Additionally, geometries of the pure Si clusters in different charge states taken from previous studies 31,34,37,42,44,[70][71][72][73] are used as starting structures on which the Cr atom is added at various positions or an atom of the Si frame is replaced by a Cr atom. These structures are subsequently optimized in different multiplicities, from the singlet to the septet state for systems with an even number of electrons, and from the doublet to the octet state for systems with an odd number of electrons.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…This area is the largest in terms of the number of related publications and includes 91 articles, namely [ 1 , 2 , 3 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ,…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
“…As for the publications devoted to the structure and dynamics of inorganic compounds, for most of them the objects of study were substances that, in principle, can be classified as clusters in the broad sense of the word; these are [ 105 , 109 , 115 , 116 , 120 , 122 , 123 , 124 , 126 , 159 ]. In five of these ten articles [ 115 , 116 , 120 , 124 , 159 ], the objects of study were elemental gold nanoparticles (which, in principle, can be considered as large clusters, in the narrow sense of the word, due to the presence of metal–metal chemical bonds in their structural units), which were either in a free state [ 115 , 124 , 159 ] or were covered with a layer of some chemical compound (i.e., they were the core of the “core-shell” system [ 116 , 120 ]).…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research about configurations, stabilities and electronic structures of MSi 15 and MSi 16 (M = Sc, Ti, V, Cr, Mn, Fe, Co, Ni) has shown that TiSi 16 and TiSi 15 show outstanding stabilities and large HOMO-LUMO gaps in this series [9]. For Zr atoms, the structural evolution of Zr-doped Si n clusters ZrSi n 0/À/2À (n = 6-16) has been investigated both theoretically and experimentally, and the ZrSi 15 has been proved to have impressive chemical and thermodynamic stability [10]. The growth processes of WSi n (n = 6-16) clusters have been explored and the WSi 15…”
Section: Introductionmentioning
confidence: 99%